Monocyte Chemotactic Protein-Induced Protein 1 (MCPIP-1): A Key Player of Host Defense and Immune Regulation - Jin, Zhuqing; Zheng, En; Sareli, Candice; Kolattukudy, Pappachan E.; Niu, Jianli (Frontiers in Immunology, 2021)
Inflammatory response is a host-protective mechanism against tissue injury or infections, but also has the potential to cause extensive immunopathology and tissue damage, as seen in many diseases, such as cardiovascular diseases, neurodegenerative diseases, metabolic syndrome and many other infectious diseases with public health concerns, such as Coronavirus Disease 2019 (COVID-19), if failure to resolve in a timely manner. Recent studies have uncovered a superfamily of endogenous chemical molecules that tend to resolve inflammatory responses and re-establish homeostasis without causing excessive damage to healthy cells and tissues. Among these, the monocyte chemoattractant protein-induced protein (MCPIP) family consisting of four members (MCPIP-1, -2, -3, and -4) has emerged as a group of evolutionarily conserved molecules participating in the resolution of inflammation. The focus of this review highlights the biological functions of MCPIP-1 (also known as Regnase-1), the best-studied member of this family, in the resolution of inflammatory response. As outlined in this review, MCPIP-1 acts on specific signaling pathways, in particular NFκB, to blunt production of inflammatory mediators, while also acts as an endonuclease controlling the stability of mRNA and microRNA (miRNA), leading to the resolution of inflammation, clearance of virus and dead cells, and promotion of tissue regeneration via its pleiotropic effects. Evidence from transgenic and knock-out mouse models revealed an involvement of MCPIP-1 expression in immune functions and in the physiology of the cardiovascular system, indicating that MCPIP-1 is a key endogenous molecule that governs normal resolution of acute inflammation and infection. In this review, we also discuss the current evidence underlying the roles of other members of the MCPIP family in the regulation of inflammatory processes. Further understanding of the proteins from this family will provide new insights into the identification of novel targets for both host effectors and microbial factors and will lead to new therapeutic treatments for infections and other inflammatory diseases.